2006
DOI: 10.1128/iai.00466-06
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison and Correlation of Neisseria meningitidis Serogroup B Immunologic Assay Results and Human Antibody Responses following Three Doses of the Norwegian Meningococcal Outer Membrane Vesicle Vaccine MenBvac

Abstract: The prediction of efficacy of Neisseria meningitidis serogroup B (MenB) vaccines is currently hindered due to the lack of an appropriate correlate of protection. For outer membrane vesicle (OMV) vaccines, immunogenicity has primarily been determined by the serum bactericidal antibody (SBA) assay and OMV enzyme-linked immunosorbent assay (ELISA). However, the opsonophagocytic assay (OPA), surface labeling assay, whole blood assay (WBA), and salivary antibody ELISA have been developed although correlation with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 47 publications
4
14
1
2
Order By: Relevance
“…This lack of linear correlation contrasts to what has been observed in adult humans for anti-DOMV IgG [41, 42] and anti-serogroup C capsule IgG [43]. Several factors may account for this difference: i) differences between human and murine immune system; ii) antibodies directed towards a wider range of antigens elicited by NOMV compared to DOMV; iii) the different nature of the antigens themselves, particularly in the case of MenC polysaccharide and fHbp (a polysaccharide and a protein, respectively).…”
Section: Discussioncontrasting
confidence: 96%
“…This lack of linear correlation contrasts to what has been observed in adult humans for anti-DOMV IgG [41, 42] and anti-serogroup C capsule IgG [43]. Several factors may account for this difference: i) differences between human and murine immune system; ii) antibodies directed towards a wider range of antigens elicited by NOMV compared to DOMV; iii) the different nature of the antigens themselves, particularly in the case of MenC polysaccharide and fHbp (a polysaccharide and a protein, respectively).…”
Section: Discussioncontrasting
confidence: 96%
“…In summary, killing of meningococci by whole blood and/or plasma can be rapid (<1 hr), effective (≥99%) and was 4- to 6-fold more frequent than an SBA titer ≥1:4. Similar results were observed in earlier studies by other investigators using slightly different whole blood killing assays [48-51]. The data support the hypothesis that many adults with SBA titers <1:4 are immune from developing meningococcal disease.…”
Section: Experimental Studiessupporting
confidence: 91%
“…Bactericidal antibody decay in adults and adolescents in this study is similar to that demonstrated following three doses of the NIPH vaccine MenBvac 17 25. Following MenBvac, a titre ≥4 was demonstrated in 57% of English adults and 50% of Norwegian adults 12 months after three doses, and in 28% of Norwegian adolescents 10 months after three doses 17 19 25. Other experience using MeNZB demonstrated similar results in Norwegian adults of whom 60% had a titre ≥4 twelve months after three doses 19.…”
Section: Discussionsupporting
confidence: 83%
“…Although a variation in absolute bactericidal titres between laboratories was demonstrated, the proportion with a bactericidal antibody titre ≥1:4 remained relatively constant 14 22. Bactericidal antibody decay in adults and adolescents in this study is similar to that demonstrated following three doses of the NIPH vaccine MenBvac 17 25. Following MenBvac, a titre ≥4 was demonstrated in 57% of English adults and 50% of Norwegian adults 12 months after three doses, and in 28% of Norwegian adolescents 10 months after three doses 17 19 25.…”
Section: Discussionsupporting
confidence: 67%